Effects of 60Co gamma radiation on eggs of tasar silkworm, Antheraea proylei (Lepidoptera) - N. Ibotombi2, O. Premila Chanu1* and (Journal of Experimental Sciences, 2011)
The radiosensitivity in eggs of tasar silkworm, Antheraea proylei (Lepidoptera) was studied by analyzing the frequency of embryonic deaths, larval survivability, moulting, larval durations, stage lethalities, growth of hatched larvae, green and dry cocoon weights. The embryonic lethalities expressed in LD50 value was found to be 13 Gy at 12 hours after oviposition. The larval lethality up to maturation of hatched larvae increase as the dose is increased in general. Whereas, survivality of hatched larvae from treated eggs with 10 Gy is even higher than control samples. The larval durations in treated samples also show excellent results in 10 Gy samples. Total larval durations are shorter in treated samples than normal samples. The larval growth generally retards when dose increases. The green and dry cocoon weights harvested from 11 Gy treated samples unusually show significant vigour than normal samples at 5% level of significance.